2016
DOI: 10.1039/c6ce01608a
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the growth of black phosphorus crystals

Abstract: The growth of high-quality black phosphorus crystals is very important to further study the physical properties of two-dimensional black phosphorus exfoliated from bulk crystals. Herein, we designed a series of experiments to fully understand the growth of black phosphorus crystals and then explore the roles of metals (or alloys) and I elements in its growth process. Finally, we developed a general approach to grow black phosphorus in high yield with high quality and low cost. The work introduced here sheds li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
61
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 30 publications
7
61
0
2
Order By: Relevance
“…Subsequently, the morphology and crystalline structure of the bulk BP was further characterized using a transmission electron microscope (TEM) image. As shown in Figure 1c,d, a ribbon-like structure was clearly observed with a clear lattice spacing of 0.218 nm, corresponding to the (002) planes of BP crystals, which is good in relation to previously reported values of BP single crystals [21][22][23]. To further confirm the characteristics of the BP crystals, selected area electron diffraction (SAED) was conducted ( Figure 1e, upper right inset of Figure 1d), which demonstrated the excellent crystallization of the corresponding materials.…”
Section: Synthesis Of High-quality Bp Single Crystalssupporting
confidence: 89%
See 1 more Smart Citation
“…Subsequently, the morphology and crystalline structure of the bulk BP was further characterized using a transmission electron microscope (TEM) image. As shown in Figure 1c,d, a ribbon-like structure was clearly observed with a clear lattice spacing of 0.218 nm, corresponding to the (002) planes of BP crystals, which is good in relation to previously reported values of BP single crystals [21][22][23]. To further confirm the characteristics of the BP crystals, selected area electron diffraction (SAED) was conducted ( Figure 1e, upper right inset of Figure 1d), which demonstrated the excellent crystallization of the corresponding materials.…”
Section: Synthesis Of High-quality Bp Single Crystalssupporting
confidence: 89%
“…Furthermore, the XRD pattern of the bulk BP crystalline, presented in Figure 1g, revealed that the preferred growth crystallographic planes were all (0k0) planes in which the peaks were mainly located at~16 • , 34 • , and 52 • , corresponding to characteristic diffraction peaks of (020), (040), and (060) planes of orthorhombic BP (space group Cmca (no. 64)) [21][22][23]. Therefore, it can be concluded that BP single crystals were successfully fabricated using this mineralization route, endowing the possibility of precise analysis and application without purification in the future.…”
Section: Synthesis Of High-quality Bp Single Crystalsmentioning
confidence: 92%
“…In addition to the Sn–I based reaction systems, a recent study shows that some other transition metals, like Pb, can fully or partially substitute Sn for the synthesis of BP crystals . Noteworthily, current studies reveal that iodine is an indispensable element in CVT based synthesis of BP, where iodine presents in forms of iodide or I 2 …”
Section: Cvt Based Synthesis Of Black Phosphorusmentioning
confidence: 92%
“…They believed that P–Sn–I compounds were first formed and then functioning as growth sites of BP. Later on, a series of experiments, by replacing Sn with other metals, such as Pb, Bi, and Cd, were performed . Interestingly, it was found that metallic Pb could replace Sn as an additive for BP synthesis.…”
Section: Cvt Based Synthesis Of Black Phosphorusmentioning
confidence: 99%
See 1 more Smart Citation